Small Intestinal Submucosa Implantation for the Possible Treatment of Vocal Fold Scar, Sulcus, and Superficial Lamina Propria Atrophy. (February 2016) - Pitman, Michael J.; Cabin, Jonathan A.; Iacob, Codrin E.
Objectives: Evaluate the histologic effects of grafting porcine-derived small intestinal submucosa (SIS) into the vocal fold superficial lamina propria (SLP) layer for the potential treatment of vocal fold scar, sulcus and superficial lamina propria atrophy. Methods: Small intestinal submucosa was implanted into the right vocal fold SLP of 6 mongrel dogs. The left vocal fold served as a sham surgical control. At 2, 4, and 6 weeks postoperative, bilateral vocal fold specimens were evaluated histologically. Results: At 2 and 4 weeks, respectively, SIS-implanted vocal folds demonstrated moderate and mild inflammation and acute and chronic inflammation. At 6 weeks, inflammation was minimal and chronic. The 6-week specimens showed copious amounts of newly generated hyaluronic acid (HA) within the graft. There was no reactive fibrosis at 6 weeks. Conclusions: In the canine model, SIS appears safe for SLP grafting. Inflammation is similar to that of sham surgery. Small intestinal submucosa results in newly generated HA without concomitant fibrosis. Small intestinal submucosa has potential to be used in treatment of disorders with SLP, including vocal fold scar, sulcus, and atrophy. Studies evaluating the effect of SIS implantation on vocal fold function, as well as the ultimate fate of the graft, are required.